Analisis Pengaruh Variabel Marketing Mix terhadap Keputusan Nasabah Melakukan Pengajuan Pembiayaan Mitraguna Berkah pada PT. BSI KCP Lubuk Sikaping - Resti Fauziah; Jon Kenedi (Universitas 45 Surabaya, 2024)
The influence of the marketing mix on consumer choices to apply for partner financing at BSI KCP Lubuk Suhuing is the driving force for this research. Seven independent factors are used in this research: product, price, promotion, location, people, process, and physical persistence. The dependent is the customer's decision to apply for Mitraguna Berkah financing. This research focuses on the results influence of the marketing mix carried out by BSI KCP Lubuk Suhuing in influencing customers to apply for Mitraguna Berkah financing using the 7P elements. Data This research used 178 BSI KCP Lubuk Suhuing clients as research samples, and data was collected through distributing questionnaires. Quantitative analysis is the analytical technique used, including validity and reliability tests, classical assumption tests, t and f tests, and the coefficient of determination (R^2). The research results show that the dependent variable, namely the customer's decision to apply for Mitraguna Berkah (Y) financing, is simultaneously influenced by independent variables which include product (X1), price (X2), promotion (X3), place (X4). ), people (X5), processes (X6), and physical persistence (X7). Based on the comparison of values, it is obtained that F_(count>) F_(table ) is f_(count )(5.524 > f_(table )(2.06) meaning that the seven variables influence the customer's decision to apply for blessing partner financing at BSI KCP Lubuk Suhuing. From The seventh most influential variable is promotion. It can be seen that the t_(count) value is 4.074.